The effect of measurable and regular exercise on ovariectomized Sprague Dawley rats in improving skin quality - Lutfi Nurdian Asnindari; Sri Kadarsih Soejono; . Hariyadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
The decline of estrogen level causes various skin changes including amount of fibroblast, the thickness of epidermis and dermis. Physical exercise is believed can increase the estrogen level and give benefit impacts on skin. It mechanism is often associated with the increase of extragonadal aromatization and estrogen serum, the activation of insulin-like growth factor (IGF), and the expression of estrogen receptor (ER). This study was conducted to investigate the effect of physical exercise in ovariectomized rat on the amount of fibroblast, the thickness of epidermis and dermis, the levels of ER β in skin and serum estrogen. Eight female Sprague Dawley rats aged 3 months were used in this study. Rats were divided into two groups i.e. Group 1 consisted of ovariectomized rats without physical exercise and Group 2 consisted of ovariectomized rats and given measurable and regular physical exercise. Rats ran on treadmill with the speed 18 m/min, the tilt of 5%, duration for 60 min/experiment/day, 5 times a week for 12 weeks. The amount of fibroblast, the thickness of epidermis and dermis, the levels of ERβ in skin and serum estrogen were measured after physical exercise. The result showed that there was a significant difference amount of fibroblast between group 1 and group 2 (p<0.05). However, no significant difference the levels of serum estrogen, ERβ, and the thickness of epidermis and dermis between Group 1 and Group 2 (p>0.05). There was a significant positive correlation between the level of serum estrogen and the thickness of epidermis (p<0.05), and negative correlation between the serum estrogen level and the level of ERβ (p<0.05), and negative significant correlation between the level of ERβ and the thickness of epidermis (p<0.05).  In conclusion, the amount of dermal fibroblast of ovariectomized rats increase after underwent measurable and regular exercise. There is correlation between the serum estrogen level and  the thickness of epidermis as well as ERβ.